2010
DOI: 10.3899/jrheum.091265
|View full text |Cite
|
Sign up to set email alerts
|

Uncoupling of Collagen II Metabolism in Newly Diagnosed, Untreated Rheumatoid Arthritis Is Linked to Inflammation and Antibodies Against Cyclic Citrullinated Peptides

Abstract: These results suggest that cartilage collagen formation and degradation are unbalanced when RA is diagnosed. The different associations of collagen II anabolism (PIIANP) and collagen II degradation (CTX-II) with anti-CCP, synovitis, and radiographic progression indicate that at this early stage of RA, cartilage collagen degradation is mainly driven by synovitis, while anti-CCP antibodies may interfere with cartilage regeneration by inhibiting collagen IIA formation. Trial registration j.nr NCT00209859.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
16
0

Year Published

2011
2011
2017
2017

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 13 publications
(16 citation statements)
references
References 45 publications
0
16
0
Order By: Relevance
“…However, the CIMESTRA study reports on a correlation between markers of cartilage catabolism (Ctelopeptide of collagen II) and disease [42]. DAS 28 and CRP represent systemic inflammation beyond the single joint examined in MRI and are not specific; involvement of MCP II was an inclusion criterion in the present study and severe inflammation of other joints did not lead to exclusion.…”
Section: Discussionmentioning
confidence: 76%
“…However, the CIMESTRA study reports on a correlation between markers of cartilage catabolism (Ctelopeptide of collagen II) and disease [42]. DAS 28 and CRP represent systemic inflammation beyond the single joint examined in MRI and are not specific; involvement of MCP II was an inclusion criterion in the present study and severe inflammation of other joints did not lead to exclusion.…”
Section: Discussionmentioning
confidence: 76%
“…There was no difference between anti-CCP-positive and anti-CCP-negative patients with respect to demographic or clinical variables, except that anti-CCP-positive patients had fewer tender joints [8 (5-15) vs 11 (7)(8)(9)(10)(11)(12)(13)(14)(15)(16); p = 0.02] and were more frequently carriers of the SE [82/93 (88%) vs 34/65 (52%); p < 0.001] compared with anti-CCP-negative individuals.…”
Section: Rheumatologymentioning
confidence: 99%
“…Thus, Turesson, et al recently reported increased COMP levels in individuals who developed RA within 1-2 years, and elevated COMP was more likely in anti-CCP-negative subjects than in anti-CCP-posi tive individuals 11 . We recently reported that the N-propeptide of collagen IIA (PIIANP), a marker of cartilage collagen anabolism, is significantly lower in anti-CCP-positive compared to anti-CCP-negative patients with RA 12 . As well, we found a negative correlation between PIIANP and anti-CCP titer in serum 12 .…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Furthermore, galectin-3 was associated with bone marrow edema score of the wrist at baseline and remained elevated during 12 months of follow-up despite a targeted, synovitis-suppressive treatment strategy [15]. Conversely, we have previously reported that a seromarker of cartilage regeneration (type IIA collagen N-terminal propeptide (PIIANP)) is decreased in newly diagnosed RA [1618] while hyaluronan (HYA), a marker of synovial swellings, is increased [19, 20]. …”
Section: Introductionmentioning
confidence: 99%